LA IMPLEMENTACIÓN DE LAS TECNOLOGÍAS DE GESTIÓN DE CALIDAD Y SU RELACIÓN CON LA INNOVACIÓN/5. IMPLEMENTATION OF QUALITY MANAGEMENT TECHNOLOGIES AND THEIR RELATIONSHIP TO INNOVATION (Revista científica Pensamiento y Gestión, 2011)
Resumen Este escrito integra estrategia y mejoramiento, al vincular innovación y calidad en las organizaciones colombianas. Se hace una revisión de los marcos teóricos existentes sobre los dos conceptos para luego explorar en 6670 empresas, la relación existente entre la inversión en tecnologías de gestión de calidad y obtención de resultados de innovación haciendo. Los resultados indican que en Colombia, las certificaciones de calidad no son una ventaja competitiva que permita lograr resultados en innovación. AbstractThis writing integrates strategy and improvement, when linking innovation and quality in the Colombian organizations. A revision of the existent theoretical framework is made on the two concepts it stops then to explore in 6670 companies, the existent relationship among the investment in technologies of management of quality and obtaining of innovation results making. The results indicate that in Colombia, the certifications of quality are not a competitive advantage that allows to achieve results in innovation.